Cultural encounters: the impact of the inquisition in Spain and the New World - Perry, Mary Elizabeth; Cruz, Anne J. (Publications of the Center for Medieval and Renaissance Studies, 1991)
More than just an expression of religious authority or an instrument of social control, the Inquisition was an arena where cultures met and clashed on both shores of the Atlantic. This pioneering volume examines how cultural identities were maintained despite oppression.Persecuted groups were able to survive the Inquisition by means of diverse strategies - whether Christianized Jews in Spain preserving their experiences in literature, or native American folk healers practicing medical care. These investigations of social resistance and cultural persistence will reinforce the cultural significance of the Inquisition.